Concurrent semantics for structured design methods - Nixon, Patrick (Trinity College Dublin, Department of Computer Science, 1996)
Design methods can be ambiguous due to dierent interpretations of symbols or concepts. This paper presents a formal semantics for the Ward/Mellor Structured Analysis Method for Real Time systems. These semantics ensures that an unambiguous meaning can be attributed to a particular design. Specically, it ensures that concurrent and real-time properties of the design can be captured and analysed. This paper concentrates on the concurrent properties.
Also in Jelly, I., Gordon, I., & Groll, P. Software Engineering for Parallel and Distributed Systems. London: Chapman Hall.
Keywords: Structured methods; Concurrency; Real-time systems